The Role of Sports Facility Management in Supporting Competitive Tennis Player Development - Hakim, Hikmad; Sahabuddin, Sahabuddin; Bismar, Ahmad Rum (Universitas Majalengka, 2025)
This study explores the relationship between strategic sports management and athlete performance enhancement through organisational effectiveness within the tennis program at the Faculty of Sports Science and Health (FIKK), Universitas Negeri Makassar (UNM). Amid growing expectations for competitive achievement in university-level sports, there is an urgent need to optimise performance through efficient management practices. Using a mixed-method approach involving surveys, interviews, document analysis, and performance metrics, this study evaluates how five key dimensions of strategic management—planning, leadership, coordination, monitoring, and resource allocation—affect athlete outcomes. Quantitative data were collected from 32 student-athletes and eight coaching staff using structured questionnaires and performance monitoring over 12 months. Qualitative insights were gathered through in-depth interviews and analysis of institutional documents. The findings revealed that leadership (Mean = 4.20) and strategic planning (Mean = 4.12) were the most influential factors contributing to performance improvements. Coordination (Mean = 3.98) and monitoring (Mean = 4.05) showed moderate effectiveness, while resource allocation scored the lowest (Mean = 3.67), indicating existing logistical challenges. Statistical regression analysis demonstrated that organisational effectiveness significantly mediated the relationship between strategic management and athletic performance, accounting for 62.3% of the variance in athlete improvement outcomes (p < 0.01). Key performance indicators showed a 50% increase in match win rate, a 27% improvement in serve accuracy, an 8.4% gain in VO₂ max, and a 20.6% rise in athlete motivation scores throughout the study. This research provides empirical evidence that effective sports management strategies can drive meaningful enhancements in athlete performance when supported by well-structured organisational systems. It offers a replicable model for academic sports institutions aiming to balance education and elite performance. The study concludes with recommendations for refining resource allocation, fostering interdepartmental collaboration, and strengthening leadership pipelines in sports programs.